Assessment of IL28 (rs12980275) and (rs8099917) Frequency in Recurrent Ocular Herpes Simplex Virus (HSV) Infection - Borivoje Savic; Bozidar Savic; Tanja Kalezic; Bojana Dacic-Krnjaja; Veljko Milosevic; Sanja Petrovic Pajic; Vesna Maric; Tiana Petrovic; Svetlana Stanojlovic (Life)
(1) Introduction: The main way of spreading the herpes simplex virus 1 (HSV-1) is through direct contact, as the virus enters the host via mucous membranes. Ocular infection can occur as a primary infection or as a recurrent one. The movement of HSV-1 along the ophthalmic branch of the fifth cranial nerve from its latency phase in the trigeminal ganglion and its activation represent a process influenced by various symbiotic factors, such as environmental conditions and the host’s genetic characteristics. The aim of this study was to assess the frequency of IL28 (rs12980275) and (rs8099917) in recurrent ocular HSV infections. (2) Materials and methods: The study included 60 patients aged over 18, of both sexes, all of whom had a history of herpes simplex labialis (HSL). Patients were tested for HSV-1-specific IgG antibodies, and seropositive individuals were genotyped for single nucleotide polymorphisms (SNPs) rs12980275 and rs8099917. A total of 57 seropositive patients were included in the study. (3) Results: A statistically significant association was found between recurrent HSV keratitis (HSK) and heterozygous GT rs8099917 and homozygous TT rs8099917, as well as heterozygous AG rs12980275 and homozygous AA rs12980275 (p < 0.01). Interestingly, patients with homozygous GG polymorphism for both genotypes GG rs8099917 and GG rs12980275 did not develop recurrent HSV keratitis. (4) Conclusion: The most frequent SNP variations in patients with recurrent HSV disease were heterozygous AG rs12980275 (61.40%) and heterozygous GT rs8099917 (52.63%). Patients with recurrent HSV keratitis lacked the homozygous GG polymorphism in both GG rs8099917 and GG rs12980275 genotypes, suggesting that HSV-seropositive individuals expressing these genotypes may have lower predisposition to develop recurrent stromal HSV keratitis.